Ensino/aprendizagem de leitura e a questão dos gêneros do discurso: aspectos teórico-aplicados - Pereira, Rodrigo Acosta (Linguagens & Cidadania, 2017)
Researches and discussions about language teaching have been presented through different perspectives in the area of Applied Linguistic (AL) (Almeida Filho, 2000; Celani, 2000; Jurado & Rojo, 2006; Kleiman, 2006; Motta-Roth, 2005; Moita Lopes, 2006; Signorini, 2006;). Among the several theoretical and methodological aspects approached by AL, the reading teaching has been represented an important role. Based on that, the present work aims to (a) discuss about the teaching reading theories; (b) present theoretical and methodological aspects concerning the concept and functionality of discourse genres according to the Discourse Analysis from Mikhail Bakhtin and (c) explain the contribution of discourse genres to the teaching/learning of reading.